Efektivitas Kebijakan Penyuluhan Pertanian pada Pemberdayaan Petani Bawang Merah di Desa Rejoso Kabupaten Nganjuk - Aulia Igga Meichasari; Widyawati Widyawati; Dandy Patrija Wirawan (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the effectiveness of agricultural extension policy in empowering shallot farmers in Rejoso Village, Nganjuk Regency. The background of this research is based on the importance of agricultural extension as a public policy instrument that functions to enhance farmers’ knowledge, skills, and independence. Although extension programs have been routinely implemented, their effectiveness needs to be evaluated to ensure that the policy truly addresses the needs and problems faced by farmers in the field.This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and documentation studies, then analyzed thematically using data reduction, data presentation, and inductive conclusion-drawing techniques. Data validity was tested through source and method triangulation. The results show that the agricultural extension policy in Rejoso Village is considered effective based on the five indicators of public policy effectiveness proposed by Riant Nugroho, namely accurate policy, accurate implementers, accurate targets, supportive environment, and proper process. The extension materials are relevant to farmers’ needs, the implementers possess adequate technical competence, and the program successfully reaches active shallot farmers. A strong socio-institutional environment, supported by farmer associations, contributes to effective implementation, although ecological challenges such as extreme weather and pest attacks remain. The extension process is systematic and participatory, covering stages of planning, implementation, assistance, and evaluation. Overall, the agricultural extension policy in Rejoso Village has improved the capacity and independence of shallot farmers. However, strengthening the number of extension workers, digitalizing evaluation systems, and providing entrepreneurship training are necessary to ensure the sustainability of policy effectiveness.